DEVELOPING STUDENTS SPEAKING SKILL FOR PRIMARY SCHOOL CHILDREN - Turejanova Shaxnoza, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Its better to say the methods of teaching speaking is studied insufficiently and require more attention to develop attention to develop speaking production and methodological development.Since the dialogues of young children continues to grow and develop without stopping, they have the ability to receive new information much faster than adults whose dialogue is fully formed. Planning is appropriate. For instance, the use of speaking activities,improvisations, role-plays, debates and story-telling is an effective way to teach a foreign language to children of preschool age.